Upaya Meningkatkan Prestasi Belajar Siswa Matematika Melalui Strategi Pembelajaran Tutor Sebaya Dalam Penguasaan Bangun Datar Kelas VI SD Hidayatur Rohman Surabaya - Denok Julianingsih (Edumatika : Jurnal Riset Pendidikan Matematika, 2018)
The problem that existed in the sixth-grade students at SD Hidayatur Rohman is that there are any students who consider that the math lesson is an elusive lesson. If the student does not understand the lessons in the class, the student does not want to ask the teacher or even feel ashamed and afraid of the teacher. For that need to apply learning strategies that can help students who experience psychological problems that are with peer tutoring strategy. The purpose of this research is to make the achievement of learning mathematics which can be increased through peer tutor learning strategy in the two-dimensional subject. The method used in this research is the method of documentation, test method, and observation. While data analysis techniques using test of student learning outcomes, analysis mastery learning, analysis of students and teachers’ observation sheet, and analysis of learning outcomes increasing. The subject of this research is the students of grade VI SD Hidayatur Rohman Surabaya. From the results of data analysis and conclusion then obtained the results of the test in the first cycle with an average score of 58.85 students while the average at the end of the second cycle of 74.47 billion of 26.54%. This learning is done with the completeness of student learning outcomes in the classical 80.95% is very feasible 47.62% above the predetermined indicator, which is equal to 75%. While the percentage of students activeness in the classical as much as 80,95% and activeness of teacher equal to 91,25% can be used in learning cycle II can increase according to indicators which have been determined.